Quality of life and the sense of happiness in native Greeks, Pontic repatriated and Albanian immigrant - Πράπας Χρήστος; Μαυρέας Βενετσάνος (The Greek Review of Social Research, 2016)
The purpose of this article was to explore indigenous perceptions, immigrants from Albania and returnees from the former Soviet Union, on the quality of life, life satisfaction and sense of happiness. The participants included 303 (58.3%) Greeks, 114 (21.9%) immigrants from Albania and 103 (19.8%) Pontic repatriated. Of these, 257 (49.4%) were male, and 263 (50.6%) women with a mean age 36.3 years, range 18-64 years. The concept of quality of life was examined by the Quality of Life Questionnaire (WHOQOL, WHO, 1993, pp. 1-7), which assesses Physical, Psychological-emotional, Interpersonal and Social Welfare. The subjective sense of happiness was assessed by Affect Balance Scale (Bradburn, 1969, pp.78), and "Satisfaction with Life Scale (Diener, 2000, pp. 40). The results showed disparity in the quality of life and life satisfaction among natives, immigrants from Albania and repatriates from the former Soviet Union, while no significant differences were found in the perception of happiness. Regardless, the Albanian immigrants seem to reflect a higher level of interpersonal and social quality of life in comparison to Pontic repatriated.